Psychometric analysis of the Behavioral Cost Scale of green purchaise in Mexico - Palacios-Delgado, Jorge (2021)
The purpose of this study was to obtain validity evidence based on the internal structure and based on a criterion and reliability estimated of the scores derived from the Green Purchasing Behavioral Cost Scale in a sample of 221 participants between 17 and 62 years old (M = 25,57; SD = 10,8) in México. Data analysis revealed an unidimensional structure that characterizes green purchasing behavioral cost and acceptable internal consistency (alfa = .75; omega = .75); confirmatory factor analysis showed optimal fit of the data to the model. Additionally the behavioral cost scores distinguish between individuals with low pro-environmental actions from those who perform actions in favor of the environment. The discussion analyzes the utility of the results for assessment of personal cost within responsible behavior with the environment, as well as the implications for future research into the pro-environmental and economic psychology.